Opening of microcracks and air permeability in concrete - Stehlík, Michal; Heřmánková, Věra; Vítek, Lubomír (Journal of Civil Engineering and Management, 2015)
The aim of this paper is to evaluate the suitability of the Torrent method of determining air permeability of concrete for an approximate assessment of damage to the surface layer of concrete caused by microcracks. The combined measurement of deformation and air permeability by means of Torrent method and of the width of microcracks on the tested concrete cubes during loading in the splitting tensile test contributed to the clarification of certain facts. The use of Torrent method seems to be more suitable in reinforced concretes where it is possible to anticipate a slower opening of cracks during the increase of load. In spite of that, the testing of these concretes is limited by the maximum dimensions of cracks, i.e. 0.075–0.1 mm in the width and 60 mm in the length. Exceeding these limit dimensions causes a massive decrease in vacuum and subsequent separation of the adhering bell of the Torrent tester.